2021
DOI: 10.3390/rs13193944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tropospheric Mismodelling in GNSS Precise Point Positioning: A Simulation Study Utilizing Ray-Traced Tropospheric Delays from a High-Resolution NWM

Abstract: In GNSS analysis, the tropospheric delay is parameterized by applying mapping functions (MFs), zenith delays, and tropospheric gradients. Thereby, the wet and hydrostatic MF are derived under the assumption of a spherically layered atmosphere. The coefficients of the closed-form expression are computed utilizing a climatology or numerical weather model (NWM) data. In this study, we analyze the impact of tropospheric mismodelling on estimated parameters in precise point positioning (PPP). To do so, we mimic PPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In other words, the wet MF which still depends on the elevation angle only, takes into account the deviation from a spherically layered atmosphere. Based on the PPP simulation results presented in Zus et al (2021), it can be concluded that the modification of the wet MF can significantly reduce the errors of the estimated zenith delays and heights. However, they used 𝐶 as 0.0031 in gradient MF at the modification step.…”
Section: Modified Wet Mapping Functionmentioning
confidence: 98%
See 4 more Smart Citations
“…In other words, the wet MF which still depends on the elevation angle only, takes into account the deviation from a spherically layered atmosphere. Based on the PPP simulation results presented in Zus et al (2021), it can be concluded that the modification of the wet MF can significantly reduce the errors of the estimated zenith delays and heights. However, they used 𝐶 as 0.0031 in gradient MF at the modification step.…”
Section: Modified Wet Mapping Functionmentioning
confidence: 98%
“…MF coefficients, 𝑎, 𝑏 and 𝑐, are estimated using non-linear least square estimation. In this study, we followed the same strategy as in Zus et al (2021) with only small modification in the quality check step.…”
Section: Tropospheric Delaymentioning
confidence: 99%
See 3 more Smart Citations